Analysis of anti-BZR1 antibody reveals the roles BES1 in maintaining the BZR1 levels in Arabidopsis - Jeong, Yu Jeong; Corvalán, Claudia; Kwon, Soon Il; Choe, Sunghwa (Journal of plant biology = Singmul Hakhoe chi, 2015)
The transcription factor brassinazole-resistant 1 (BZR1) is a key component and positive regulator of the brassinosteroid (BR) signaling pathway. In this study, we report the cloning, expression, and purification of BZR1 for preparation of rabbit antibody against BZR1. The full-length coding sequence of BZR1 was cloned into the pET28a cloning vector and expressed in Escherichia coli to produce recombinant His-tagged BZR1. Using affinity chromatography with Ni-NTA beads under denaturing conditions, we were able to purify an approximately 38-kD recombinant His-BZR1 fusion protein, which was used to raise antiserum against BZR1. The antibody titer and sensitivity were evaluated by indirect ELISA and immunoblot. Furthermore, the antibody was used to detect protein from extracts derived from plant tissues, and was able to detect three major forms of BZR1 in Arabidopsis plants as well as in other three monocot species rice, Setaria viridis and sorghum. The produced anti-BZR1 antibody will be instrumental in determining the molecular mechanisms underlying BZR1 activity. Thus, we believe that our antibody represents a powerful tool for analyzing the role of BZR1 in plant physiology and characterizing the crosstalk between proteins in signaling cascades involving BZR1 in dicot and monocot plants.